Pengaruh Media Pembelajaran Berbasis Wordwall Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Putri, Megawati; Usman, Asep; Nasrullah, Yufi (Universitas Garut, 2024)
The background of this research is the lack of learning innovations used by teachers in learning activities and the lack of students' ability to achieve maximum results in Islamic Religious Education subjects. One of these things is influenced by learning activities where some students cannot operate the application, this is due to a lack of adequate facilities and infrastructure when learning takes place. In addition, it was seen that students were less enthusiastic when the teacher delivered learning material. Therefore, the researcher was motivated to conduct research at the school.The purpose of this study was to find out (1) how to use wordwall-based learning media at SMPN 1 Karangtengah Garut, (2) how student learning outcomes at SMPN 1 Karangtengah Garut, and (3) how wordwall-based learning media influences student learning outcomes in subject of Islamic Religious Education at SMPN 1 Karangtengah Garut. The method used in this study is a quantitative method with descriptive survey analysis techniques, namely research taken based on phenomena that occur by making decisions from sample data using statistical tests. By describing or describing phenomena. In this study, a population of 28 respondents was used with a sample using the Nonprobability Sampling technique of 28 respondents. The results obtained include (1) there is an influence of wordwall-based learning media at SMPN 1 Karangtengah Garut with an average percentage score of 75.8% in the Good category. (2) the learning outcomes of students at SMPN 1 Karangtengah Garut with an average percentage score of 79.0% are in the Good category. (3) The effect of wordwall-based learning media on student learning outcomes in PAI subjects at SMPN 1 Karangtengah Garut with results t count > t table (5.496 > 2.056) This means that H1 is accepted H0 is rejected. With a percentage of 53.74%, while 46.25% is influenced by other factors such as the student's living environment, parental support as well as guidance from competent teachers.